Seeing 'the unseen hand': Celebrity, promotion and public relations. (May 2017) - Fitch, Kate
Public relations scholars have largely neglected celebrity public relations. The aim of this article is to explore public relations activity associated with celebrity, in order to better understand day-to-day public relations work and its influence on contemporary culture. Positioning public relations in terms of its cultural intermediary role, this article considers the work of celebrity publicists and public relations agencies that work closely with celebrities. It identifies the increased visibility of public relations in contemporary society, the links between public relations and promotional culture, and public relations' role in media production and consumption. The findings point to the need to reconceptualise public relations as a promotional practice and call for a renewed focus on the societal impact of public relations activity.